Innovation of an android-based beverage sales application using a design thinking approach for MSME digitalization in Nabire - Arfan, Usman; Rony, Heris Yosua Ramase (Priviet Social Sciences Journal, 2026)
Digital transformation has become an essential requirement for Micro, Small, and Medium Enterprises (MSMEs) to improve competitiveness and operational efficiency. This study aims to design an Android-based beverage sales application prototype to support MSME digitalization in Nabire Regency. The research employed the Design Thinking approach, consisting of empathize, define, ideate, prototype, and test stages. Activity diagrams were used to model the application’s business processes, while the prototype was developed using Figma as an interactive and visual system representation. Usability evaluation was conducted through limited testing using the Single Ease Question (SEQ) and System Usability Scale (SUS). The results indicate that the proposed prototype provides a clear user flow, aligns with user needs, and achieves a good level of usability. The developed prototype can serve as a foundation for future implementation of an Android-based beverage sales application to support MSME digitalization in Nabire Regency.